2012
DOI: 10.1021/ac2032244
|View full text |Cite|
|
Sign up to set email alerts
|

Lithium/Sulfur Cell Discharge Mechanism: An Original Approach for Intermediate Species Identification

Abstract: The lithium/sulfur battery is a promising electrochemical system that has a high theoretical capacity of 1675 mAh g(-1), but its discharge mechanism is well-known to be a complex multistep process. As the active material dissolves during cycling, this discharge mechanism was investigated through the electrolyte characterization. Using high-performance liquid chromatography, UV-visible absorption, and electron spin resonance spectroscopies, we investigated the electrolyte composition at different discharge pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
928
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(995 citation statements)
references
References 37 publications
52
928
2
2
Order By: Relevance
“…Some literature suggests that the transition from the high to the low discharge voltage plateau happens concurrently with the start of the formation of solid Li 2 S 2 and Li 2 S 6, 14. This stage contributes to the major portion of the capacity with a fixed voltage.…”
Section: Theoretical Capacity Fade Analysis Of Li–s Batteriesmentioning
confidence: 98%
See 1 more Smart Citation
“…Some literature suggests that the transition from the high to the low discharge voltage plateau happens concurrently with the start of the formation of solid Li 2 S 2 and Li 2 S 6, 14. This stage contributes to the major portion of the capacity with a fixed voltage.…”
Section: Theoretical Capacity Fade Analysis Of Li–s Batteriesmentioning
confidence: 98%
“…The ultimate discharge products are insoluble and nonconductive Li 2 S 2 /Li 2 S; however, there are a number of intermediate soluble products with different Li to S ratios (Li 2 S x , 3 ≤ x ≤ 8) 6. For one thing, the nonconductive sulfur (S 8 ) and Li 2 S 2 /Li 2 S greatly decrease the utilization of the active sulfur materials and pose major issues for power capability 7.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Multiple literature reports have reached different conclusions on the existence of the solid, electrolyte-insoluble species Li 2 S 2 and whether it forms as a solid intermediate during the discharge of Li-S batteries. [5][6][7][8][9][10][11][12] Recent studies have suggested there may be separate reaction pathways that are followed at different points during Li-S discharge: one where only Li 2 S is formed during reduction of soluble polysulfides (Li 2 S x , x > 2), and a second where both Li 2 S and Li 2 S 2 are formed simultaneously. 11 The question of whether any Li 2 S 2 that forms can then be reduced is debated in the literature.…”
mentioning
confidence: 99%
“…3. As shown in Fig.3(a), three cathodic peaks are observed at 2.45, 2.05, and 1.9 V during the discharge process, showing typical sulfur cathode charge/discharge behavior [14,24]. Firstly, elemental sulfur in the solid phase is dissolved in the electrolyte, and then it is reduced to S 6 2-, S 4 2-, and S 2 2-(S 2-), respectively.…”
Section: Resultsmentioning
confidence: 93%